Canine distemper virus (CDV) transit through the americas: need to assess the impact of CDV infection on species conservation (2020)
Canine Morbillivirus (also known as Canine Distemper Virus—CDV) is the causative agent of one of the most important diseases in domestic dogs and wild fauna. It belongs to the Paramyxoviridae family, order Mononegavirales, which has a non-segmented, single-stranded linear negative polarity RNA genome (Lamb and Parks, 2013). The clinical disease is characterized by moderate to severe respiratory signs, gastrointestinal issues, immune suppression, and/or neurological disease (De Vries et al., 2015; Pfeffermann et al., 2018).